2015
DOI: 10.1039/c5ay00020c
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical deoxyribonucleic acid biosensor for rapid genotoxicity screening of chemicals

Abstract: A schematic diagram of the E-DNA biosensor detection of PCDD by DPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6] Wu et al suggested a sensitive electrochemical biosensor for detection of double-stranded deoxyribonucleic acid. 7 Li et al reported a uorescence biosensor with an ultra-low limit of detection for folate receptors, which can be used for the observation of early cancer. 8 In addition, Shtenberg et al studied nanostructured porous Si sensors for the detection of heavy metal ions in water by immobilising horseradish peroxidase, laccase and multi-copper oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Wu et al suggested a sensitive electrochemical biosensor for detection of double-stranded deoxyribonucleic acid. 7 Li et al reported a uorescence biosensor with an ultra-low limit of detection for folate receptors, which can be used for the observation of early cancer. 8 In addition, Shtenberg et al studied nanostructured porous Si sensors for the detection of heavy metal ions in water by immobilising horseradish peroxidase, laccase and multi-copper oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…MB is often used for the description of the DNA damages caused by chemical factors. Thus, changes in the DNA intercalation and substitution of MB molecules with genotoxic species was recorded using voltammetric techniques for the assessment of polychlorinated dibenzodioxins, dibenzofurans and related compounds .…”
Section: Resultsmentioning
confidence: 99%
“…Following rinsing, the electrodes were cleaned ultrasonically three times with ethanol followed by Milli-Q water. They were then electrochemically activated in 0.5 mol L −1 H 2 SO 4 by potential scanning between 0 and 1.7 V until a repeatable CV was achieved, after which they were thoroughly washed with Milli-Q water and dried under a nitrogen stream [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%